Respuesta :

Answer:

[tex]( 2 , \frac{1}{2} )[/tex]

Step-by-step explanation:

A(-2, 4) , B(6, -3)

[tex]\boxed{midpoint = ( \frac{x1 + x2}{2}, \frac{y1 + y2}{2}) }[/tex]

Midpoint between points A and B

[tex] = ( \frac{ - 2 + 6}{2} , \frac{4 - 3}{2} )[/tex]

[tex] = ( \frac{4}{2} , \frac{1}{2} )[/tex]

[tex] = (2 , \frac{1}{2} )[/tex]

840060

Answer:

The midpoint between A and B is a point with coordinates (2, 0.5).

Step-by-step explanation:

The "y" coordinate of the midpoint will be equal to the sum of A's and B's y coordinates divided by 2,  and the x coordinate of the midpoint will be equal to the sum of A's and B's x coordinates divided by 2.

x coordinate of the midpoint = (6 - 2) / 2 = 4 / 2 = 2

y coordinates of the midpoint = (4 - 3) / 2 = 1 / 2 = 0.5

Therefore midpoint between A and B is a point with co0rdinates (2, 0.5).